Analisis Wacana Kritis Lirik Lagu Kartonyono Medhot Janji (Kartonyono De Yakusoku O Yabutta) Versi Bahasa Jepang - Teguh Santoso; Althaf Gauhar Auliawan; Hendrike Priventa (ICHIGO : Jurnal Bahasa, Sastra, Pendidikan, dan Budaya Jepang, 2024)
The study referred to as "Critical Discourse Analysis of the Lyrics of the Japanese Version of the Song Kartonyono Medhot Janji" is the title of this research. In this research, the qualitative descriptive approach uses facts or phenomena that have been used empirically by researchers to tell what happened. The aim of this research is to study text analysis of the Japanese version of the song Kartonyono de Yakusoku o Yabutta. Next, social cognition analysis of the lyrics translated into Japanese by Ryuu Hikaru on his YouTube channel, which comes from a Javanese pop song created by Denny Caknan, as well as the social context in which the song appeared. This study analyzes the Japanese version of the text, or song lyrics. Critical discourse analysis of the text (song lyrics), social cognition and social context is analyzed using Teun A. van Dijk's discourse analysis model.